Bis{μ-2,2′-[o-phenylenebis(nitrilomethylidyne)]diphenolato}dicopper(II) N,N′-dimethylformamide disolvate - Yu, Guofeng (International Union of Crystallography, 2008)
The title compound, [Cu(2)(C(20)H(14)N(2)O(2))(2)]·2C(3)H(7)NO, consists of a centrosymmetric dimer composed of two copper(II) ions and two tetradentate salphen ligands {H(2)salphen is 2,2′-[o-phenylenebis(nitrilomethylidyne)]diphenol}, and two dimethylformamide solvent molecules. The Cu(II) atom is bonded to two N imino atoms and three phenolate O atoms of salphen. One deprotonated phenol group of each ligand bridges two Cu atoms, forming the dimer. The geometry about the five-coordinate Cu atom can best be described as slightly distorted rectangular pyramidal. The crystal structure is stabilized by π–π interactions [centroid-centroid distance 3.779 (2) Å] and C—H⋯O hydrogen bonds.